Catheter Management and Risk Stratification of Patients With in Inpatient Treatment Due to Acute Epididymitis - Wenzel, Mike; Deuker, Marina; Welte, Maria N.; Hoeh, Benedikt; Preisser, Felix; Homrich, Till; Kempf, Volkhard A. J.; Hogardt, Michael; Mandel, Philipp; Karakiewicz, Pierre I.; Chun, Felix K. H.; Kluth, Luis A. (Frontiers in Surgery, 2020)
Objective: To evaluate catheter management in acute epididymitis (AE) patients requiring inpatient treatment and risk factors predicting severity of disease. Material and Methods: Patients with AE and inpatient treatment at the University Hospital Frankfurt were analyzed between 2004-2019. A risk score, rating severity of AE, including residual urine >100ml, fever >38.0°C, C-reactive protein (CRP) >5mg/dl, White blood count (WBC) >10/nl, was introduced. Results: Of 334 patients, 107 (32%) received a catheter (transurethral [TC]: n=53, 16%, suprapubic [SPC]: n=54, 16%). Catheter patients were older, exhibited more comorbidities and had higher CRP and WBC compared to the non catheter group (NC). Median length of stay (LOS) was longer in the catheter group (7 vs. 6 days, p<0.001), whereas necessity of abscess surgery and recurrent epididymitis did not differ. No differences in those parameters were recorded between TC and SPC. According to our established risk score, 147 (44%) patients exhibited 0-1 (low-risk) and 187 (56%) 2-4 risk factors (high-risk). In high-risk group, patients received a catheter significantly more often than in low-risk (TC: 22% vs. 9% SPC: 19% vs. 12%, both p≤0.01). Catheter or high-risk patients exhibited more frequently positive urine cultures than NC or low-risk patients. LOS was comparable between high-risk patients with catheter and low risk NC patients. Conclusion: Patients with AE, who received a catheter at admission were older, multimorbid and exhibited more severe symptoms of disease compared to NC patients. A protective effect of catheters might be attributable in patients with adverse risk constellation or high burden of comorbidities. The introduced risk score indicates a possibility for risk stratification.